Matemática financeira com abordagem em educação financeira para o Ensino Médio - Castro, Héwerton Alves Martins de (2016)
Our motherland’s current economic situation makes us reflect on the importance of studying the Financial Education since elementary school, so that we can educate our younger generation to make our country a healthier financially. This dissertation discusses many distinguished fashions for teaching high school students on how to invest, finance and, above all, getting them to know the investment funds that are used the most in our country. After being familiarized with these investment funds, the young students will learn the importance of saving and investing. Methods like Newton’s linear approximation will help in their financial calculations, as well as making them acquainted with a fundamental tool for this field. The study of amortization systems will help students acknowledge our country’s most common financing choices, especially regarding the purchase of their first car or real estate. The methodology chosen for this dissertation was essentially a bibliographical research. In conclusion, with the help of examples and exercises with a focus on the daily life, there will be a greater interest among kids and teenagers in learning Financial Mathematics and its application in the most diverse situations